Effects of climate change on the development of Hopea ferrea in tropical forests - Nguyen, Minh Duc; Nguyen, Phan Lan Hong; Nguyen, Giang Son; Bui, Thi Tuyet Xuan; Nguyen, Thi Phuong Trang; Vu, Dinh An; Hoang, Thi Nga; Nguyen, Minh Tam (Vietnam Journal of Biotechnology, 2025)
Hopea ferrea (Dipterocarpaceae) is one of the valuable timber trees that is distributed in the rainforests of southern and central Vietnam. This species is threatened due to its overexploitation and destruction of habitats. In order to determine the effects of global climate change on the species, we analyzed 225 H. ferrea trees from eight natural populations covering the distribution range in Vietnam using eight polymorphic microsatellite markers. We detected low genetic distances for population pairs in the same area (average of 0.045) and high genetic distances for population pairs between different areas (average of 0.213). Similarly, high genetic identity for population pairs in the same areas (average of 0.956) and low genetic identity for population pairs between different areas (average of 0.811). We detected the genetic relationships among eight populations based on analyses of a neighbor-joining and principal coordinates. The clustering analysis showed that all populations in the same area were grouped together to form a distinct cluster. We detected the two or three genetic groups based on the genetic differentiation among populations. With two genetic groups, the first group included the three populations in the Highlands, and the second included all populations in the two areas of southeast and center. With the three genetic groups, first group included the three populations in Highlands; the second group included three populations in the southeast area; and the third group included two populations in the central area. The approximate Bayesian computation showed that H. ferrea populations diverged during the last glacial maximum.